The impact of LDC graduation on trade: A quantitative assessment - Eddy Bekkers; Gianmarco Cariola (World Trade Organization (WTO), 2022)
Several Least-Developed Countries (LDCs) will graduate from the LDC status in the coming decade implying that they will lose preferential access to export markets. We quantify the expected impact of LDC graduation on exports of graduating and non-graduating LDCs incorporating detailed preference utilization data in a partial equilibrium model. We compare the results under actual and full preference utilization rates. Separately, we explore how underutilization of tariff preferences affects the exports of countries benefiting from such preferences. The analysis generates four main results. First, according to our projections, graduation will have a negative impact on the exports of graduating LDCs (more than US 6 billion export loss or 6% of exports), especially in the clothing sector. Second, the adverse trade effects of graduation would be overestimated by 30% under full instead of actual utilization rates. Third, our projections suggest that the increase in exports of non-graduating LDCs following graduation of other LDCs would be limited, implying that non-graduating poorer LDCs may hardly benefit from graduation of richer LDCs. Fourth, our projections suggest that increasing the utilization of LDC preferences would have positive trade effects. The exports of LDCs would increase by almost US 7 billion if they simultaneously switched to a full utilization regime.
Keywords: F13; F17; O19; 330; LDC graduation; tariff preferences; partial equilibrium model